Students' perceptions of problem-based learning in ESP teaching in higher education - Kranjec, Katja (Vestnik za tuje jezike, 2025)
To address the ever-increasing need for more learner-centred teaching approaches in higher education, a study was conducted to explore students’ perceptions of problem-based learning (PBL) in an English for Specific Purposes (ESP) course at the Faculty of Public Administration, University of Ljubljana. This was the first time students experienced this approach in their classes at the faculty. 73 responses to an open-ended question about PBL were analysed, applying text mining techniques conducted in the Orange software tool. First, the most frequent words and phrases expressed in students’ responses were determined and visualized using a word cloud. Next, sentiment analysis was carried out to identify the emotional tone behind the responses, further enhanced by an analysis based on Ekman’s model to discern dominant emotions. Finally, key themes were aligned with theoretical concepts of PBL and divided into positive and negative categories. More than 95% of students’ responses were overwhelmingly positive, expressing feelings of joy and high satisfaction with the new method. Even though students’ perceptions may be influenced by various factors, such as the quality of teaching, the rapport between the teacher and the students as well as the students’ background, the findings of this study suggest that PBL may be very effective in ESP teaching, particularly in the field of public administration. Learning evolves through solving real-life problems, providing ample opportunities to develop language skills relevant to students’ needs and future endeavours.
Keywords: angleščina za posebne namene; English for Specific Purposes (ESP); learner-centred teaching; na učenca osredotočeno poučevanje; problem-based learning (PBL); problemsko učenje; problem-solving skills; skupinsko delo; team-work; veščine reševanja problemov